2023
DOI: 10.3390/su151813588
|View full text |Cite
|
Sign up to set email alerts
|

Digital Economy, Clean Energy Consumption, and High-Quality Economic Development: The Case of China

Zhong Ren,
Jie Zhang

Abstract: The digital economy has become an important force driving China’s socio-economic development. From the perspective of sustainable energy development and based on China’s provincial panel data from 2011 to 2020, this paper probes into the relationship and transmission mechanism of digital economy, clean energy consumption, and high-quality economic development and utilizes the spatial Durbin model and intermediary effect model to carry out empirical tests on the paths of their influence. The results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Wu et al (2023) found that the DE can improve energy efficiency and promote sustainable urban development [26]. Ren and Zhang (2023) also gave recognition to this view from the Chinese provincial level [27].…”
Section: Literature Review and Mechanism Construction 21 Literature R...mentioning
confidence: 99%
“…Wu et al (2023) found that the DE can improve energy efficiency and promote sustainable urban development [26]. Ren and Zhang (2023) also gave recognition to this view from the Chinese provincial level [27].…”
Section: Literature Review and Mechanism Construction 21 Literature R...mentioning
confidence: 99%
“…Digital transformation is the use of digital intelligence to upgrade or reengineer a business to achieve business growth and efficiency improvements, thereby contributing to sustainable development [17]. Currently, we are in the era of the digital economy, with the continuous development of digital technology represented by big data and artificial intelligence, and digital transformation has become the path to high-quality development [18,19]. Digital transformation not only poses a technological challenge, but also plays an irreplaceable role in greening the transition and promoting green development [20].…”
Section: Introductionmentioning
confidence: 99%
“…Ethical dilemmas arise from biased algorithms and the potential misuse of technology, impacting fairness and justice (Guo et al 2023). Electronic waste and the substantial energy footprint of digital infrastructure add a layer of environmental concerns that we must address (Ren and Zhang 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This marks a unique era characterised by innovation and efficiency, transcending traditional limitations, and presenting nations across the globe with an unprecedented opportunity for accelerated economic growth (Guo et al 2023). Navigating and leveraging the possibilities presented by this interconnected and digitally driven world is, therefore, paramount (Ren and Zhang 2023). A nuanced understanding of the multifaceted dimensions of global economic growth within the digital sphere is essential to harnessing its full potential (Yu and Zhou 2021).…”
Section: Introductionmentioning
confidence: 99%